Codex and Roll in the New Testament - McCown, C. C. (Harvard theological review, 1941)
During the last twenty or thirty years evidence has been rapidly accumulating to prove that the codex was in general use for books at a much earlier time than was formerly supposed. The definite testimony of Martial and others on the subject could be misinterpreted, discounted, or overlooked so long as there was no clear corroborating archaeological evidence. Papyrus and the roll had taken firm hold upon the classicistic imaginations of modern students of ancient literatures, especially after the nineteenth-century discoveries of papyri in Egypt, and no one dreamed that the New Testament documents could have been written originally on anything but papyrus sheets and papyrus rolls.